Multi criteria route determination model for blind and visually impaired people in indoor environments: A User centric approach - Fernando, Thudugala Mudalige Thushari Nimalika (Curtin University, 2022)
How to model and find indoor routes best suites diverse needs of Blind and Visually Impaired (BVI) community is an ill-defined problem. BVI indoor route determination problem is addressed using a multidisciplinary approach, given the contribution of build environment, BVI user perspective, and the route optimization contexts to the problem. A multi-objective route determination model, alone with underlying indoor building and route models witch support deriving BVI friendly routes are designed, using a user-centric approach.